2014
DOI: 10.1002/pros.22829
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pulsed electromagnetic field therapy on prostate volume and vascularity in the treatment of benign prostatic hyperplasia: A pilot study in a canine model

Abstract: BACKGROUNDBenign prostatic hyperplasia (BPH) is a result of urogenital aging. Recent studies suggest that an age-related impairment of the blood supply to the lower urinary tract plays a role in the development of BPH and thus may be a contributing factor in the pathogenesis of BPH. The canine prostate is a model for understanding abnormal growth of the human prostate gland. We studied the efficacy of pulsed electromagnetic field therapy (PEMF) in dogs to modify prostate blood flow and evaluated its effect on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…In particular, a pre-clinical study demonstrated the effectiveness of PEMF therapy in reducing PV in dogs affected by BPH. 37 To the best of our knowledge, only two human studies have used PEMF in the treatment of BPH. 23,24 So far, different devices have been used for PEMFs therapy, tailoring treatment duration according to tissue-specific conductivity and field strengths produced by the device used.…”
Section: Kidney Functionmentioning
confidence: 99%
“…In particular, a pre-clinical study demonstrated the effectiveness of PEMF therapy in reducing PV in dogs affected by BPH. 37 To the best of our knowledge, only two human studies have used PEMF in the treatment of BPH. 23,24 So far, different devices have been used for PEMFs therapy, tailoring treatment duration according to tissue-specific conductivity and field strengths produced by the device used.…”
Section: Kidney Functionmentioning
confidence: 99%
“…However, few studies quantified the biochemical constituents in seminal plasma of healthy dogs (England & Allen, ; Mann & L‐Mann, ) or dogs with prostatic diseases (Motheo et al., ). The biochemical assessment of the canine prostatic fluid may help to identify possible biomarkers of prostatic diseases and may provide important benefits for human medicine (Aquino‐Cortez, Silva, Araújo, Menezes, & Moura, ), as the dog is used as an experimental model for the study of prostatic diseases in men (Leoci, Aiudi, Silvestre, Lissner, & Lacalandra, ).…”
Section: Introductionmentioning
confidence: 99%
“…The employ of an anti‐oestrogenic compound, tamoxifen citrate, is also reported in the literature; it gives a competitive block on oestrogen receptors with a mixed agonist‐antagonist mechanism (Corrada et al, ). Moreover, some authors suggest the use of plants extract to treat BPH (Odenthal, ), while others demonstrated the efficacy of pulsed electromagnetic field therapy on BHP in dogs with no apparent side effects (Leoci, Aiudi, Silvestre, Lissner, & Lacalandra, ). When large cysts are present, the surgical treatments proposed in literature are drainage, resection of the cyst with or without drainage placement, omentalization, marsupialization and partial or total prostatectomy (Smith, ).…”
Section: Benign Prostatic Hyperplasiamentioning
confidence: 99%
“…Moreover, some authors suggest the use of plants extract to treat BPH (Odenthal, 2017), while others demonstrated the efficacy of pulsed electromagnetic field therapy on BHP in dogs with no apparent side effects (Leoci, Aiudi, Silvestre, Lissner, & Lacalandra, 2014).…”
Section: Doberman German Shepherd Rhodesian Ridgeback and Labradormentioning
confidence: 99%